Long-term growth response of Norway spruce in different mounding and vegetation control treatments on fine-textured soils - Uotila, Karri; Luoranen, Jaana; Saksa, Timo; Laine, Tiina; Heiskanen, Juha (Finnish Society of Forest Science, 2022)
Mechanical site preparation (MSP) is a common practice that precedes the planting of Norway spruce (Picea abies (L.) H. Karst.) in Nordic forests. Mounding has become the most used method in spruce planting in recent years. This study examined the effects of different mounding treatments (spot and ditch mounding, inversion, unprepared control with or without herbicide application) and a mechanical vegetation control (MVC) treatment done 3–4 years after planting on the post-planting growth of spruce container seedlings and their development to saplings during the first 11–13 years on two forest till soils in central Finland, one on flat terrain and other on a southwest slope. On these fine-textured soils the spot and ditch mounding methods favoured spruce saplings development. Inversion and unprepared plots showed weakest growth. On the site with flat terrain, 11 years post planting, spruce saplings were 78–144 cm (38–80%) taller and their breast height diameters were 11–13 mm (60–74%) thicker for ditch or spot mounding than for inversion or herbicide treatment. On the site with sloped terrain the differences were minor between the MSP treatments. MVC improved spruce height growth on sites which did not have intensive MSP, especially on control saplings planted on unprepared soil in herbicide and inversion treatments. On the flat terrain, MVC reduced the density of resprouts to be removed later in pre-commercial thinning. As a conclusion, spot or ditch mounding favoured the growth of spruce over inversion especially on flat terrain with fine-textured soil.
Keywords: maanmuokkaus; heinäntorjunta; metsäkuusi; boreal forest; establishment; fine-textured soils; mechanical vegetation control; plantation; regeneration; scarification; tree growth; site preparation